Anti-PD-1 Monotherapy in Advanced Melanoma—Real-World Data from a 77-Month-Long Retrospective Observational Study - Kuzmanovszki, Daniella; Kiss, Norbert; Tóth, Béla; Kerner, Tünde; Tóth, Veronika; Szakonyi, József; Lőrincz, Kende; Hársing, Judit; Imrédi, Eleonóra; Pfund, Alexa; Szabó, Ákos; Brodszky, Valentin; et al. (Biomedicines, 2022)
Real-world evidence plays an important role in the assessment of efficacy and safety of novel therapies. The increasing use of immune checkpoint inhibitors (ICIs) in patients with advanced melanoma has led to notably improved clinical outcomes, while they are also associated with immune-related adverse events (irAEs). The majority of the available data are based on clinical trials, where the investigated subjects often do not adequately represent the general patient population of the everyday practice. Although there is a niche of objective biomarkers for the future treatment response of ICIs, certain studies suggest that irAEs may be predictive. The aim of this study was to carry out a retrospective analysis of treatment data from patients with advanced melanoma, treated with a single anti-PD-1 agent (pembrolizumab or nivolumab) during a 77-month-long period. Treatment efficacy and occurrence of adverse events were analyzed to identify potential predictive markers. Primary and secondary endpoints were the overall survival (OS) and progression-free survival (PFS). In our cohort, we demonstrated that the occurrence of more than one irAE showed a correlation with response to PD-1 ICI therapy and improved the OS and PFS. Our study suggests, that the grade of toxicity of the irAE may affect the survival rate.